Penguatan Usaha UMKM Baby Crab di Kota Banda Aceh Melalui Edukasi Sistem Jaminan Halal - Hasni, Dian; Lubis, Yanti Meldasari; Noviasari, Santi; Novita, Melly; El Husna, Nida (Universitas Syiah Kuala, 2023)
Halal food is food that does not contain elements or ingredients that are haram or prohibited for consumption by Muslims, both regarding food raw materials, food additives, others auxiliary materials and whose management is carried out in accordance with the provisions of Islamic religious law. In Indonesia, processed food is required to have a halal label. This regulation is regulated as a form of protection for Indonesian citizens, in accordance with the implementation of Article 29 paragraph 2 of UUD 1945. Regulation of halal labels on processed food is carried out based on UU No. 33 of 2014. Furthermore, to guarantee the traceability of halal labels on processed food is regulated by halal certification system. This certification is an acknowledgment of the halalness of a product issued by the Halal Product Assurance Organizing Body (BPJPH). Unfortunately, this certification system is still not widely known by food producers, especially MSMEs, which has an impact on limiting sales of their products and reducing its potential markets. This service activities aim to provide an understanding of the importance of halal guarantee certification for BABY CRAB SMEs in Aceh City. This activities consists of several stages, started from interview, kitchen visit, material presentation and discussions related to assistance in preparing administrative requirements. The partners of this service activity stated that this socialization fostered a strong desire for partners to take care of the halal guarantee certification of their products as soon as possible. From the visiting and discussion, it can be recommended that our partner is ready and able to provide all admnistrative requirements to apply halal certification